Geomorphic Classification of the Catastrophic Flood Effects of the Gadar River Based on the Mitzen Model - mojtaba yamani; mosa abbasi (نشریه جغرافیا و برنامه‌ریزی, 2020)
Introduction Hard floods increase the strength of canals, erosion rates and sedimentation in the rivers. Late in the evening and early morning of April 26, 2016, the Gadar basin experienced lightning and hard storms directly across the basin, causing only a few hours of rainfall in the basin. Due to the high rainfall of April 1976 with a maximum of 197 mm, the soil was saturated and caused direct runoff to the canals. The flood caused significant biological and geomorphic disturbances in the riverbeds, which caused complete loss of vegetation in some parts of the river. Even in the areas where the alluvium was left, many plants were destroyed. The floods caused major changes in the morphology of the Gadar main waterways and rivers, which have been unprecedented in recent decades. This study aimed to provide a model to determine the amount of geomorphic turbulence caused by catastrophic flood in the Gadar River during the flood event of 96 years. Data and Methology  The data were collected from library methods, statistical data, imagery and field surveys. Aerial photographs were selected to determine the extent of geomorphic perturbations caused by the catastrophic flood at 35 km from the main river before and after the flood. Post-flood morphological changes using aerial imagery revealed that digitizing the area where catastrophic flood perturbations occurred along the Gadar River was clearly visible. For the essential management using the Mitsen model, recurrent periods including 100 and 500 years flood bed and flood plain were used to determine the geomorphic turbulence of the river.                                      In the disturbance area of ​​the riverbank, the highest amount of disturbance was in group 4 (10965793 m 2) and the lowest was in group 5 (657247 m 2). These large-scale patterns are also consistent with increasing river distances for 100- and 500-year flood return periods. The highest amount of geomorphic perturbation was related to Class D covering a total of 4972105 square meters, while Class B perturbation with an area of ​​578969 square meters covered the least perturbation. The highest amount of geomorphic perturbations belonged to Group A for flood bed area with 46.58% covering an area of ​​about 1694712 m 2 while the lowest D perturbation was with Group 57 with 3.57%. The total area is 178931 square meters. For the 100 and 500 year floodplains, similar to the floodplain area, the highest and lowest turbulence rates belonged to Group A and B, respectively. Results and Discussions Most of the perturbations and locations with maximum geomorphic perturbations were caused by catastrophic flooding of the Gadar River. within the flood bed area and these perturbations for all groups of the river bed and geomorphic The distance from the river and the movement to the 100- and 500-year floodplain returns decreases. This trend is particularly evident in most of the river and geomorphic turbulence. There is a particular trend between groups 1, 2 and 3 of the perturbation and the geomorphic groups B and C that place the subduction sites in this perturbation group. Floods have the capacity and ability to transport moderate amounts of sediment or moderate erosion, but as a large force that can completely erode alluvial riverbeds and remove vegetation, it is not sufficient so it will be just outside the flood plain erosion threshold This is probably due to increased plant resistance and root reinforcement and its effect on floodplain roughness and decreased bed flow velocity. Most floodplain erosion occurred in the bed and adjacent to the canal of the study. Since floodplain erosion involves the riverbank and geomorphic sections, the most severe type of D-group geomorphic perturbation process was approximately 58% with two groups of 4 and 5 rivers, respectively, as partial and complete flood plain erosion, respectively.                                                                   By comparing the native Gadder model with the Mitzen model, it can be seen that the Gadar River indigenous classification model is similar in some respects to that of the Mitzen, but also has some differences. In the Mitzen model, the topographic features, river cover, anthropogenic disturbance and the geomorphic disturbance of the bed sediment and the morphology of the river are not fully considered while in the Gadar basin the presence of lands adjacent to the riverbed. The river bed with different coverages along with the sediment type of the bed and banks plays an important role in the extent of flood control or expansion. Conclusion Most of the disasters caused by the catastrophic floods in the Gadar River include Group 5 for river disruption and Group D for geomorphic disruption, which occurred mainly in the floodplain area, which is confined to all river banks and geomorphic section distances from the river. And the movement toward the 100- and 500-year flood plain return periods has declined. In group 5, 90.2% of the turbulence occurred in the floodplain, while only 8.6% occurred in the 100-year floodplain and 0.6% in the 500-year floodplain. Similarly, in Group D, 92% of the geomorphic turbulence occurred in the floodplain, and only 8% of the turbulence occurred in the other floodplain groups, so most of the severe turbulence was in the canal bed and less severe turbulence mainly in the The 100- and 500-year flood plain return periods are located outside the flood plain.